SOME CONSIDERATIONS ON TURKESTAN AUTONOMY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article describes in detail the creation of the Turkestan autonomy, its composition and activities. It was also thought that the February Revolution of 1917 brought great changes to the life of Turkestan, that after the revolution many political organizations and parties advocating for independence and freedom were created in Turkestan, and that the progressive intelligentsia began to demand autonomy for Turkestan.